(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article presents some initiatives undertaken by the theater critic Bárbara Heliodora as a director of the National Theater Service (SNT) during the first years of the military dictatorship (1964-1967). In this years, the critic gave a cultural and educational meaning to the institution’s activities, according to the ideas present in her texts and shared with other critics and professionals, changing practices carried out since its creation in the 1930s.